2008
DOI: 10.11646/zootaxa.1945.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the major African snake radiation: a molecular phylogeny of the Lamprophiidae Fitzinger (Serpentes, Caenophidia)

Abstract: The Elapoidea includes the Elapidae and a large (~60 genera, 280 sp.) and mostly African (including Madagascar) radiation termed Lamprophiidae by Vidal et al. (2007), that includes at least four major groups: the psammophiines, atractaspidines, lamprophiines and pseudoxyrhophiines. In this work, we reviewed the recent taxonomic history of the lamprophiids, and built a data set including two nuclear protein-coding genes (c-mos and RAG2), two mitochondrial rRNA genes (12S and 16S rRNA) and two mitochondrial prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
74
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 38 publications
6
74
1
Order By: Relevance
“…The constituents of new subfamily Carphophiinae (Natriciteres + Rhabdophis + Xenochrophis), as proposed by Zaher et al (2009), could not be well supported by our analyses. The placement of Lycognathophis seychellensis in Natricinae (Vidal et al, 2008) was confirmed by our c-mos data with strong nodal support. Interestingly, our c-mos results indicates Lycognathophis to be related closely to the African natricids.…”
Section: Discussionsupporting
confidence: 74%
“…The constituents of new subfamily Carphophiinae (Natriciteres + Rhabdophis + Xenochrophis), as proposed by Zaher et al (2009), could not be well supported by our analyses. The placement of Lycognathophis seychellensis in Natricinae (Vidal et al, 2008) was confirmed by our c-mos data with strong nodal support. Interestingly, our c-mos results indicates Lycognathophis to be related closely to the African natricids.…”
Section: Discussionsupporting
confidence: 74%
“…Heise et al (1995) and Pinou et al (2004) found Atractaspis to be most closely related to the Elapidae (but did not include any other atractaspidid genera in their analysis). Vidal et al (2007Vidal et al ( , 2008 placed Atractaspis (along with the genera Lamprophis, Pythonodipsas, Mehelya, Psammophylax, Pseudaspis, Buhoma, Psammodynastes, Prosymna and Leioheterodon) within the newly erected family Elapoidea, the sister group to Elapidae and the new family Lamprophiidae (corresponding closely to the Boodontinae of Lawson et al 2005). Kelly et al (2008) found that Atractaspis and several other atractaspidid genera represented a basal African radiation of colubroids, closely associated with Buhoma, Psammodynastes, and the Lamprophiidae (e.g.…”
mentioning
confidence: 99%
“…However, the only molecular phylogenetic studies to include a significant representation of atractaspidid species (Nagy et al 2005;Vidal et al 2008) found Homoroselaps lacteus to be the sister group to Atractaspis, with Macrelaps more distantly related. Homoroselaps is a problematic genus, considered on the basis of morphology to be most closely affiliated with the Elapidae by some researchers (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations